A Pangenome Approach for Discerning Species-Unique Gene Markers for Identifications of Streptococcus pneumoniae and Streptococcus pseudopneumoniae - Gonzales-Siles, Lucia; Karlsson, Roger; Schmidt, Patrik; Salvà-Serra, Francisco; Jaén-Luchoro, Daniel; Skovbjerg, Susann; Moore, Edward R. B.; Gomila, Margarita (Frontiers in Cellular and Infection Microbiology, 2020)
Correct identifications of isolates and strains of the Mitis-Group of the genus Streptococcus are particularly difficult, due to high genetic similarity, resulting from horizontal gene transfer and homologous recombination, and unreliable phenotypic and genotypic biomarkers for differentiating the species. Streptococcus pneumoniae and Streptococcus pseudopneumoniae are the most closely related species of the clade. In this study, publicly-available genome sequences for Streptococcus pneumoniae and S. pseudopneumoniae were analyzed, using a pangenomic approach, to find candidates for species-unique gene markers; ten species-unique genes for S. pneumoniae and nine for S. pseudopneumoniae were identified. These species-unique gene marker candidates were verified by PCR assays for identifying S. pneumoniae and S. pseudopneumoniae strains isolated from clinical samples. All determined species-level unique gene markers for S. pneumoniae were detected in all S. pneumoniae clinical isolates, whereas fewer of the unique S. pseudopneumoniae gene markers were present in more than 95% of the clinical isolates. In parallel, taxonomic identifications of the clinical isolates were confirmed, using conventional optochin sensitivity testing, targeted PCR-detection for the “Xisco” gene, as well as genomic ANIb similarity analyses for the genome sequences of selected strains. Using mass spectrometry-proteomics, species-specific peptide matches were observed for four of the S. pneumoniae gene markers and for three of the S. pseudopneumoniae gene markers. Application of multiple species-level unique biomarkers of S. pneumoniae and S. pseudopneumoniae, is proposed as a protocol for the routine clinical laboratory for improved, reliable differentiation, and identification of these pathogenic and commensal species.